Algumas discussões sobre a abordagem econômica do território na geografia e suas implicações no espaço rural - Fajardo, Sergio [UNESP] (My University, 2005)
The paper aims at dealing with territory notions from economical approaches, usually used in Geography. Many times, territory concepts that limit it to a physical base, superficial, of the economical processses that produce space, are predominant in studies about the spacial transformations and space production. This way, Geography adopts conceptual interpretations from natives of other fields of knowledge, from different forms of thinking and methods. Territory and territoriality escape this way from an ample reading of the space. In the case of the rural space, being greatly defined for economical elements, it has in its territoriality the presence of actions headed to the regional development. Evaluating an effective construction of the territory, constituted by the economical logic and its socio-cultural political implications about the rural space, is mainly important.
Some discussions about the economic approach of territory in geography and its implications in the rural area
Keywords: Geographic categories; Regional development; Rural space; Territory